Influence of CYP3A and ABCB1 Single Nucleotide Polymorphisms on the Pharmacokinetics/Pharmacodynamics of Tacrolimus in Pediatric Patients - Yang, Mengjie; Huan, Gui; Wang, Mei (Current Drug Metabolism, 2018)
Background: Single Nucleotide Polymorphisms (SNPs) are very common variants of many genes and are also promising markers associated with drug reactions in pharmacogenomics research. In pediatric organ transplantation, tacrolimus is a major immunosuppressive agent used to prevent organ rejection. The SNP of these genes have been studied extensively in adult population, but there is no systematic review in children. This article focuses on the effects of ABCB1 and CYP3A SNPs on tacrolimus in children who are undergoing organ transplantations. Methods: We searched the literature that provided the effect of SNP on metabolism and pharmacokinetics of tacrolimus in pediatric patients in Google, Science Direct and PubMed. Then we accessed the methods used in these studies, the sample size, the model and the conclusions they have obtained. Results: We found that there is no evidence shown that CYP3A4 SNP has an influence on the pharmacokinetic/ pharmacodynamics of tacrolimus in the population of children. Moreover, most studies have failed to find a link between the ABCB1 SNP and the pharmacokinetics of tacrolimus in children. However, although the amount of literature is limited, it does show a link between ABCB1 SNPs and tacrolimus pharmacodynamics. In addition, the literature shows a strong link between CYP3A5 SNP and pharmacokinetics of tacrolimus, but there is no direct evidence that CYP3A5 SNP has the same effect on the pharmacodynamics of tacrolimus. Conclusion: More standardized clinical trials are needed to assess the relationship between CYP3A5 SNP and tacrolimus pharmacodynamics in children, particularly in terms of acute rejection and nephrotoxicity.
Keywords: Tacrolimus